Multiple C2 domains and transmembrane region proteins (MCTPs) tether membranes at plasmodesmata. (9th July 2019) - Brault, Marie L; Petit, Jules D; Immel, Françoise; Nicolas, William J; Glavier, Marie; Brocard, Lysiane; Gaston, Amèlia; Fouché, Mathieu; Hawkins, Timothy J; Crowet, Jean‐Marc; Grison, Magali S; Germain, Véronique; et al.
Abstract: In eukaryotes, membrane contact sites (MCS) allow direct communication between organelles. Plants have evolved a unique type of MCS, inside intercellular pores, the plasmodesmata, where endoplasmic reticulum (ER)–plasma membrane (PM) contacts coincide with regulation of cell‐to‐cell signalling. The molecular mechanism and function of membrane tethering within plasmodesmata remain unknown. Here, we show that the multiple C2 domains and transmembrane region protein (MCTP) family, key regulators of cell‐to‐cell signalling in plants, act as ER‐PM tethers specifically at plasmodesmata. We report that MCTPs are plasmodesmata proteins that insert into the ER via their transmembrane region while their C2 domains dock to the PM through interaction with anionic phospholipids. A Atmctp3/Atmctp4 loss of function mutant induces plant developmental defects, impaired plasmodesmata function and composition, while MCTP4 expression in a yeast Δtether mutant partially restores ER‐PM tethering. Our data suggest that MCTPs are unique membrane tethers controlling both ER‐PM contacts and cell‐to‐cell signalling. Synopsis: Plant plasmodesmata are pore‐like cell‐to‐cell junctions containing a strand of endoplasmic reticulum (ER) in close contact to the plasma membrane (PM). The Multiple C2 domains and transmembrane region protein (MCTP) family regulates these contact sites by acting as ER‐PM tethers. Members of the MCTP family are plasmodesmata localised and act as ER‐PM tethers. MCTPs anchor in the ER through their transmembrane regions and dock to the PM through their C2 domains by interacting with anionic phospholipids. MCTP3 and MCTP4 act at plasmodesmata, and are important for plant growth and development. MCTP3 and MCTP4 impact on plasmodesmata function and molecular organisation. Abstract : Plant plasmodesmata are pore‐like cell‐to‐cell junctions containing a strand of endoplasmic reticulum in close contact to the plasma membrane. The MCTP protein family regulates these contact sites by acting as ER‐plasma membrane tethers.